2011
DOI: 10.1075/gest.11.1.01cla
|View full text |Cite
|
Sign up to set email alerts
|

Using speech and gesture to introduce new objects to young children

Abstract: Adults rely on both speech and gesture to provide children with information pertinent to new word meanings. Parents were videotaped introducing new objects to their children (aged 1;6 and 3;0). They introduce these objects in three phases: (1) they establish joint attention on an object; (2) they introduce a label for it; (3) they situate the object conceptually. Parents used labels and gestures to maintain attention on the object; with one-year-olds, they led with gestures to capture the children’s attention.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(41 citation statements)
references
References 61 publications
0
40
0
1
Order By: Relevance
“…Iconic gestures have been shown to support word learning for a range of word types in both first- (Goodrich & Kam, 2009;McGregor, Rohlfing, Bean, & Marschner, 2009) and second-language acquisition (Tellier, 2007(Tellier, , 2008. Clark and Estigarribia (2011) found that when adults teach 3-year-olds new words, adults use gestures (as well as object manipulation) to indicate parts of a novel object and to describe actions and functions. McGregor et al (2009) taught 2-year-old children the preposition term under through the modeling of objects, either with or without iconic gestures.…”
Section: Gestures and Word Learningmentioning
confidence: 99%
“…Iconic gestures have been shown to support word learning for a range of word types in both first- (Goodrich & Kam, 2009;McGregor, Rohlfing, Bean, & Marschner, 2009) and second-language acquisition (Tellier, 2007(Tellier, , 2008. Clark and Estigarribia (2011) found that when adults teach 3-year-olds new words, adults use gestures (as well as object manipulation) to indicate parts of a novel object and to describe actions and functions. McGregor et al (2009) taught 2-year-old children the preposition term under through the modeling of objects, either with or without iconic gestures.…”
Section: Gestures and Word Learningmentioning
confidence: 99%
“…point at cup þ 'cup') does not reliably predict the onset of two-word sentence-like utterances [17], reinforcing the point that it is the specific way in which gesture is combined with speech, rather than the ability to combine gesture with speech per se, which signals the onset of future linguistic achievements. The gesture in a complementary gesture þ speech combination has traditionally been considered redundant with the speech it accompanies but, gesture typically locates the object being labelled and, in this sense, has a different function from speech [36]. Complementary gesture þ speech combinations have, in fact, recently been found to predict the onset of a linguistic milestone-but they predict the onset of complex nominal constituents rather than the onset of sentential constructions.…”
Section: (Iii) Complex Nominal Constituentsmentioning
confidence: 99%
“…The gesture in a complementary gesture+speech combinational has traditionally been considered redundant with the speech it accompanies but, as Clark and Estigarribia (2011) point out, gesture typically locates the object being labeled and, in this sense, has a different function from speech. Complementary gesture+speech combinations have, in fact, recently been found to point forward—but to the onset of nominal constituents rather than to the onset of sentential constructions.…”
Section: Gesture Not Only Precedes But Also Predicts the Onset Of LImentioning
confidence: 99%